2004
DOI: 10.1182/blood-2004-03-1036
|View full text |Cite
|
Sign up to set email alerts
|

Determination of relapse risk based on assessment of minimal residual disease during complete remission by multiparameter flow cytometry in unselected patients with acute myeloid leukemia

Abstract: Quantification of minimal residual disease (MRD) reveals significant prognostic information in patients treated for acute myeloid leukemia (AML). The application of multiparameter flow cytometry (MFC) for MRD assessment has resulted in significant prognostic information in selected cases in previous analyses. We analyzed MRD in unselected patients with AML in complete remission (CR) after induction (n ‫؍‬ 58) and consolidation (n ‫؍‬ 62) therapies. By using a comprehensive panel of monoclonal antibodies we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
163
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(171 citation statements)
references
References 35 publications
7
163
0
1
Order By: Relevance
“…In CML monitoring of the BCR-ABL transcript levels is included in routine strategies in the post transplantation period to identify the need for adoptive immunotherapy or TKI treatment, 34,128 but in all other myeloid malignancies, AML, MDS and the BCR-ABL-negative CMPD, comparable approaches still have to be developed with regard to quantitative PCR, 18,20,147 multiparameter flow cytometry, [53][54][55] and interphase FISH. 45 Studies that analyze these methods for their predictive value within the post transplantation period are still limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In CML monitoring of the BCR-ABL transcript levels is included in routine strategies in the post transplantation period to identify the need for adoptive immunotherapy or TKI treatment, 34,128 but in all other myeloid malignancies, AML, MDS and the BCR-ABL-negative CMPD, comparable approaches still have to be developed with regard to quantitative PCR, 18,20,147 multiparameter flow cytometry, [53][54][55] and interphase FISH. 45 Studies that analyze these methods for their predictive value within the post transplantation period are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…80 The decrease of cells with a specific LAIP when compared at diagnosis and shortly after initial therapy correlates significantly with the achievement of CR and with survival, [53][54][55][56] and the reduction of aberrant cells to a threshold of 0.1% after chemotherapy was assessed as predictor for long-time survival in another study. 105 However, in the post transplantation setting the use of multiparameter flow cytometry still has to be validated as changes of the immunophenotype might be more frequent in relapse following SCT than after standard therapy where complete loss of the previous LAIP is seen in B25%.…”
Section: Multiparameter Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…However, increasing evidence suggests that leukemia relapse may be related to minimal residual disease (MRD), a small fraction (below the threshold of morphological detection) of leukemic cells persisting within leukemia patients after achieving CR. Since high levels of MRD are significantly associated with a high frequency of relapse and a short duration of survival, MRD has been considered an important risk factor for leukemia relapse [29,30]. It has been postulated that MRD cells adopt a drug-resistant phenotype during the course of chemotherapy and have the potential to form a regrowing leukemic population, thereby leading to leukemia relapse [31].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic impact of flow cytometry was independent of cytogenetics or other prognostically relevant parameters in multivariate analysis. 48 In addition, numerous studies demonstrated an increase of LAIP-positive cells before the occurrence of morphological relapse. In a study on 252 pediatric patients with AML, a proportion of 40.5% cells with the aberrant blast phenotype was associated with a threefold increased relapse risk when compared to patients below this threshold.…”
Section: Immunophenotypingmentioning
confidence: 99%